Abordagens distribuídas para simulação do escoamento superficial baseadas no modelo digital de elevação - Lima, Dário Macedo (2021)
Hidropixel is a simple distributed rainfall-runoff model used to estimate the direct runoff hydrograph for storm events. First, the Hidropixel model determines the flow travel time from each Digital Elevation Model (DEM) pixel to the basin outlet. Then, excess precipitation is estimated for each DEM pixel using SCS-CN method. The final direct runoff hydrograph for the entire basin is determined by the sum of the flow rate from all contributing pixels during each timestep. In this research, two methods were developed to improve the Hidropixel model: Hidropixel-TUH+ and Hidropixel-DLR. In the first one, a triangular unit hydrograph was estimated for each pixel. It was assumed that the hydrograph reaches the basin outlet after the pixel travel time. In the second method, the flow rate generated by an excess precipitation pulse reaches the basin outlet after the travel time and the final pixel hydrograph pass through a linear reservoir to represent the storage effects. The upper Medway catchment (250 km2), located to the south east of England, was used to test the methods. The results demonstrate that both methods had a good performance. The Hidropixel-DLR predicted well the shape of the hydrograph for most storm events (average Nash-Sutcliffe efficiency of 0.93), accurately reproducing the peak flow rate and the time to peak. Hidropixel-TUH+ performed worse than Hidropixel-DLR, underpredicting the peak flow rate and overpredicting the time to peak, but it also predicted well the hydrograph, with an average efficiency of 0.84.